Examining indicators of psychosocial risk and resilience in parents of autistic children - Dimachkie Nunnally, Amanda; Factor, Reina S.; Sturm, Alexandra; Valluripalli Soorya, Latha; Wainer, Allison; Taylor, Sandra; Ponzini, Matthew; Abbeduto, Leonard; Gulsrud, Amanda C. (Frontiers in Behavioral Neuroscience, 2023)
Background: Parents of autistic children experience increased levels of caregiver strain and adverse mental health outcomes, even in comparison to parents of children with other neurodevelopmental disabilities. Previous studies have largely attributed these increased levels of mental health concerns to behavioral challenges associated with their child’s autism spectrum disorder (ASD), but less attention has been given to other potential child factors, such as child adaptive functioning. Additionally, little is known about potential protective factors, such as parents’ emotion regulation abilities, that may ameliorate the experience of caregiver strain, anxiety, and depression. Objective: The current study examined the impact of child characteristics (restricted and repetitive behaviors, adaptive functioning and behavioral concerns) on parent mental health outcomes (caregiver strain, anxiety, depression and wellbeing). Additionally, we explore parents' emotion regulation abilities as a moderator of impact of child characteristic on parents' mental health outcomes. Results: Results of linear mixed effect models indicated a significant relationship between parents’ emotion regulation abilities and all four parent outcomes. Additionally, children’s adaptive functioning abilities and repetitive behaviors (RRBs) were significant predictors of caregiving strain. Parents' emotion regulation abilities were a significant moderator of the effect of children’s repetitive behaviors and adaptive functioning challenges on caregiver strain, such that better emotion regulation abilities mitigated the impact of child clinical factors on caregiver strain. Finally, a significant difference was detected for mothers’ and fathers’ mental health, with mothers reporting higher caregiver strain, and more symptoms of anxiety and depression than did fathers. Conclusions: This study leveraged a large sample of autistic children and their biological parents to examine the relationship between children’s clinical characteristics and parents' psychological wellbeing. Results indicate that, although parents of autistic children do experience high rates of internalizing mental health concerns that relate to child adaptive functioning and RRBs, parent emotion regulation abilities act as a protective factor against adverse mental health outcomes. Further, mothers in our sample reported significantly higher rates of depression, anxiety, and caregiver strain, as compared with fathers.